2019
DOI: 10.1021/acs.jpcc.9b03575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al and Al2O3 Nanoparticles on the Thermal Decay of 1,3,5-Trinitro-1,3,5-triazinane (RDX): Reactive Molecular Dynamics Simulations

Abstract: Metallic additives, Al nanoparticles in particular, have extensively been used in energetic materials (EMs), of which thermal decomposition is one of the most basic properties. Nevertheless, the underlying mechanism for the highly active Al nanoparticles and their oxidized counterparts, the Al2O3 nanoparticles, influencing the thermal decay of aluminized EMs has not fully been understood. Herein, we explore the influence of Al and Al2O3 nanoparticles on the thermal decomposition of 1,3,5trinitro-1,3,5-triazina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…The reactions occur readily because they are energy barrierfree. 33,36,37,40,41 A more remarkable reduction in the potential energy of L-ANP is observed and has a relation on a higher content of the Al@Al 2 O 3 nanoparticle, compared with H-ANP. It agrees with a previous experimental research, as a high content of Al largely facilitates to increase the heat release.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The reactions occur readily because they are energy barrierfree. 33,36,37,40,41 A more remarkable reduction in the potential energy of L-ANP is observed and has a relation on a higher content of the Al@Al 2 O 3 nanoparticle, compared with H-ANP. It agrees with a previous experimental research, as a high content of Al largely facilitates to increase the heat release.…”
Section: Resultsmentioning
confidence: 91%
“…In Figure 4,ba, some molecular fragments of RDX are adsorbed on the nanoparticle surface at 20 ps, due to the aforementioned no energy barrier. 36,37,40 Thereby, the oxide shell of the ANP is thickened. A significant disintegration and an evident void with very sparse particles are found in H-ANP at 21 ps, suggesting a fast shell crack and microexplosion of the entire ANP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the advantage of reacting with CO, HC molecules and Carbon atoms in soot and generating large amounts of oxygen, allowing the fuel to burn thoroughly [51,52]. Hao et al [53] found that aluminium (Al) nano-additives had a strong oxygen extraction ability and could significantly reduce the induction time and energy required for catalytic exothermic reactions. Singh et al [54] found that carbon-based single-walled nanotubes and multi-walled nanotubes could dramatically increase the ignition rate, ignition delay period, and extend the total combustion time.…”
Section: Nano-additives: a Very Promising Fuel Additivementioning
confidence: 99%
“…1,7,8 Generally, metals have traditionally been known to be good energy storage resources in addition to being effective additives in slurry fuels, energetic materials, and propellants by virtue of their high specic energy. 3,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The majority of prior research on harnessing the chemical energy contained in metal fuels has concentrated on the reaction of various metals, particularly aluminum (Al) and magnesium (Mg), with water to produce hydrogen on demand, with only a few studies focusing on the combustion of metal fuels to generate heat. [12][13][14] Lately, the combustion of Li with various gaseous products has piqued interest for a multitude of reasons.…”
Section: Introductionmentioning
confidence: 99%